Editorial for focused issue “Wilson Disease: from genetics to management of disease” - Weiskirchen, Ralf; Stremmel, Wolfgang (Annals of translational medicine, 2019)
Wilson disease was previously called hepatolenticular degeneration. It is a rare inherited disorder preventing the body from removing copper via bile. Accordingly, copper builds up in liver and spills over to other organs, i.e., the basal ganglia of the brain.